Non-coding RNAs (ncRNAs)-mediated high expression of Ras-related C3 botulinum toxin substrate 1 (RAC1) correlates with poor prognosis and tumor immune infiltration of liver hepatocellular carcinoma - Zhang, Tao; Jiang, Tao; Jiang, Yuting; Lang, Ren; He, Qiang (Translational Cancer Research, 2026)
Liver hepatocellular carcinoma (LIHC) is a highly malignant tumor with a poor prognosis, and there is an urgent need to identify reliable prognostic markers and therapeutic targets. Ras-related C3 botulinum toxin substrate 1 (RAC1), a key member of the Rho GTPase family, has been reported to play a role in the development of various cancers. Nevertheless, its specific regulatory mechanisms and its influence on the tumor immune microenvironment in hepatocellular carcinoma (HCC) are not yet fully elucidated. In our study, we aimed to comprehensively investigate the expression pattern, prognostic value, regulatory mechanisms and immune infiltration role of RAC1 in LIHC.